Identification and Expression Analysis of Candidate Genes Involved in Carotenoid Biosynthesis in Chickpea Seeds - Rezaei, Mohammad K.; Deokar, Amit; Tar'an, Bunyamin (Frontiers in Plant Science, 2016)
Plant carotenoids have a key role in preventing various diseases in human because of their antioxidant and provitamin A properties. Chickpea is a good source of carotenoid among legumes and its diverse germplasm and genome accessibility makes it a good model for carotenogenesis studies. The structure, location and copy numbers of genes involved in carotenoid biosynthesis were retrieved from the chickpea genome. The majority of the single nucleotide polymorphism (SNPs) within these genes across five diverse chickpea cultivars was synonymous mutation. We examined the expression of the carotenogenesis genes and their association with carotenoid concentration at different seed development stages of five chickpea cultivars. Total carotenoid concentration ranged from 22 μg g-1 in yellow cotyledon kabuli to 44 μg g-1 in green cotyledon desi at 32 days post anthesis (DPA). The majority of carotenoids in chickpea seeds consists of lutein and zeaxanthin. The expression of the selected 19 genes involved in carotenoid biosynthesis pathway showed common pattern across five cultivars with higher expression at 8 and/or 16 DPA then dropped considerably at 24 and 32 DPA. Almost all genes were up-regulated in CDC Jade cultivar. Correlation analysis between gene expression and carotenoid concentration showed that the genes involved in the primary step of carotenoid biosynthesis pathway including carotenoid desaturase and isomerase positively correlated with various carotenoid components in chickpea seeds. A negative correlation was found between hydroxylation activity and provitamin A concentration in the seeds. The highest provitamin A concentration including β-carotene and β-cryptoxanthin were found in green cotyledon chickpea cultivars.